Implementasi Model Pembelajaran Pedagogik Multiliterasi dalam Meningkatkan Berpikir Kritis Siswa di SD Negeri 1 Senyiur - Muhammad Zainul Ramdani (AS-SABIQUN, 2026)
Critical thinking ability is one of the main competencies that students need to possess because it is related to the ability to analyze, evaluate, and solve problems logically and systematically. This study aims to analyze the implementation of the multiliteracy pedagogical learning model in improving students’ critical thinking skills at SD Negeri 1 Senyiur, Keruak Subdistrict, East Lombok Regency. This study used data collection through observation, interviews, questionnaires, documentation, and critical thinking ability tests. Qualitative data were analyzed through data reduction, data presentation, and conclusion drawing, whereas quantitative data were analyzed using descriptive statistics and a paired-sample t-test assisted by SPSS version 25. The results show that the implementation of the multiliteracy pedagogical learning model was able to significantly improve students’ critical thinking skills. This was evidenced by an increase in the average critical thinking ability score from 62.45 in the pretest to 84.30 in the posttest, with a significance value of 0.000 < 0.05. In addition, students became more active in discussion, problem-solving, and information analysis activities. The conclusion of this study affirms that the multiliteracy pedagogical learning model is effective in improving students’ critical thinking skills in elementary school learning. The implications of this study indicate the importance of implementing multiliteracy learning that encourages higher-order thinking activities, active participation, and information analysis skills in the basic learning process.